A subversão das relações coloniais em o morro dos ventos uivantes: questões de gênero - Dias, Daise Lilian Fonseca (2011)
The objective of this research is to analyze Wuthering Heights (1847), written by the English writer Emily Brontë (1818-48), from a postcolonial perspective, based on Said (1994; 2003), Ashcroft et al (2004), Loomba (1998), and Boehmer (2005), among others. It is noticed that there is in the English literature a repetitive model of representation of the colonial relationships mainly until 1847, when Brontë s romance was published which praises the English people and their culture, disqualifying dark skinned people as well as their culture. Those people are, in general, represented from a negative perspective and subjugated by the English imperialism. Brontë romance subverts this kind of representation because the protagonist, a foreign gypsy, Heathcliff, reverts the socio-economical relationships imposed by his oppressors, the Englishmen who surround him and, consequently, subjugates them by an analogical way to his own experience. The novel s subversive characteristic will be highlighted, mainly the fact that the history takes place in England, which gives significance to Heathcliff s actions, since he is well succeed in something that provokes fear to English people: they become victims of dark skinned people in their own territory, England.